“A Life More Ordinary” Processes of 5-Year Recovery From Substance Abuse. Experiences of 30 Recovered Service Users - Bjornestad, Jone; Svendsen, Thomas Solgaard; Slyngstad, Tale Ekeroth; Erga, Aleksander H.; McKay, James R.; Nesvåg, Sverre; Skaalevik, Alexander Waagan; Veseth, Marius; Moltu, Christian (Frontiers in Psychiatry, 2019)
Background Studies investigating the subjective experiences of long-term recovery from substance use disorder are scarce. Particularly functional and social factors have received little attention. Objectives To investigate what long-term recovered service users found to build recovery from substance use disorder. Material and Methods The study was designed as a phenomenological investigation subjected to thematic analysis. We interviewed 30 long-term recovered adult service users. Results Themes: 1) Paranoia, ambivalence and drug cravings: extreme barriers to ending use, 2) Submitting to treatment: a struggle to balance rigid treatment structures with a need for autonomy, 3) Surrendering to trust and love: building a whole person, 4) A life more ordinary: surrendering to mainstream social responsibilities, 5) Taking on personal responsibility and gaining autonomy: It has to be me, it cannot be you. Conclusions Our study sample described long-term recovery as a developmental process from dependency and reactivity, to personal autonomy and self-agency. The flux of surrendering to and differentiating from authority appeared to be a driving force in recovery progression. Participants called for treatment to focus on early social readjustment.